Enhancing Customer Experience: Analyzing Rocket Indonesia Application Satisfaction Using SERVQUAL and IPA - Usiawan, Daniel Wibowo; Vikaliana, Resista (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study aims to analyze the level of customer satisfaction for the Roket Indonesia application. Using the Service Quality (SERVQUAL) and Importance Performance Analysis (IPA) methods, this study measures service quality and identifies priority areas for improvement. Data was collected from 133 application users, with a sample of 100 people, and analyzed using SPSS. The results show that all 12 items tested meet the criteria for validity and reliability. The GAP analysis shows that four out of 12 attributes perform beyond expectations, while the other eight attributes need to be improved. However, the overall customer satisfaction level reached 77.78%, indicating that in general, customers are satisfied with the service provided. Based on the analysis, several areas that need to be improved are consistency in delivery, ability to resolve delivery issues, and guarantee of replacement goods if goods are damaged or lost during delivery. Improvement proposals include conducting regular audits, enhancing delivery staff training, forming a special team for resolving delivery issues, implementing an efficient and responsive complaint management system, and providing a clear and transparent goods replacement policy. This research provides valuable insights for PT. TIKI Jalur Nugraha Ekakurir Tomang in their efforts to continuously meet and exceed customer expectations. Furthermore, the results of this study can be used as a basis for improving services and business strategies in the future.